Pharmacognostical and Preliminary Phytochemical Investigation of Embelia ribes Burm f - Rahul.J, Sudani R.J (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Embelia ribes burm f. is a struggling shrub, almost a climber and has been used as anthelmintic, carminative and stimulant, it is also used in treatment of abdominal disorders, lung diseases, constipation, indigestion, fungus infections, mouth ulcer, sore throat, pneumonia, heart disease and obesity. The present study was carried out to investigate morphological, microscopical, physicochemical and phytochemical screening of Embelia ribes fruits and powder. Morphological studies showed the presence of various diagnostic characters. In the microscopical studies, churna showed the presence of Stone cells of the mesocarp, sclerieds of the mesocarp, epicarp in surface view with striated cuticle, perisperm cells and cells of endosperm filled with aleurone grains and fixed oil. Ash value, extractive value, foreign organic matter and moisture content were determined for quality standard of drugs. Phytochemical investigation shows the presence of alkaloids, carbohydrate, saponins, phenolic compounds and tannins, proteins, oil and fats and mucilage. The result of the study could be useful for identification and preparation of monograph of the plant.